2008
DOI: 10.1093/jxb/erm323
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of an Auxin Response Factor in the tomato induces modification of fine pectin structure and tissue architecture

Abstract: It has previously been shown that down-regulation of an auxin response factor gene (DR12) results in pleiotropic phenotypes including enhanced fruit firmness in antisense transgenic tomato (AS-DR12). To uncover the nature of the ripening-associated modifications affecting fruit texture, comparative analyses were performed of pectin composition and structure in cell wall pericarp tissue of wild-type and AS-DR12 fruit at mature green (MG) and red-ripe (RR) stages. Throughout ripening, pectin showed a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 76 publications
5
41
0
2
Order By: Relevance
“…The auxin inhibitor p-Chlorophenoxyisobutyric acid mimics ACC treatment, confirming the antagonistic action of the two hormones during fruit ripening, and auxin delays tomato ripening by affecting a set of key factors, such as RIN, ethylene, and ABA (Su et al, 2015). Consistent with the role of auxin in fruit ripening, tomato fruit firmness was shown to be partly regulated by tomato Auxin Response Factor4 (SlARF4), a transcription factor known to mediate auxin responses Guillon et al, 2008;Sagar et al, 2013). More recently, SlARF2, a tomato auxin response factor, was described as an essential component of the regulatory network controlling fruit ripening.…”
Section: Ethylene and Other Phytohormones In Fruit Ripeningmentioning
confidence: 69%
“…The auxin inhibitor p-Chlorophenoxyisobutyric acid mimics ACC treatment, confirming the antagonistic action of the two hormones during fruit ripening, and auxin delays tomato ripening by affecting a set of key factors, such as RIN, ethylene, and ABA (Su et al, 2015). Consistent with the role of auxin in fruit ripening, tomato fruit firmness was shown to be partly regulated by tomato Auxin Response Factor4 (SlARF4), a transcription factor known to mediate auxin responses Guillon et al, 2008;Sagar et al, 2013). More recently, SlARF2, a tomato auxin response factor, was described as an essential component of the regulatory network controlling fruit ripening.…”
Section: Ethylene and Other Phytohormones In Fruit Ripeningmentioning
confidence: 69%
“…Moreover, the link between auxin biosynthesis or signaling and sugar accumulation in the fruit tissues has been highlighted by a number of studies (Pandolfini et al, 2002;Wang et al, 2009), though the mechanisms by which this hormone impacts sugar metabolism and therefore fruit quality remain poorly understood. Previous work demonstrated that DR12/ARF4, a member of the tomato ARF gene family of transcription factors, is involved in the regulation of fruit development; that is, transgenic tomato plants with decreased SlARF4 mRNA levels produced dark-green fruit at immature stages, with increased chlorophyll content, a larger number of chloroplasts, and unusual cell division at late stages of fruit development, as well as blotchy ripening and enhanced fruit firmness (Jones et al, 2002;Guillon et al, 2008). In further characterizing the role of this auxin transcriptional regulator, the current study addresses more specifically the impact of down-regulation of SlARF4 on sugar metabolism throughout fruit development.…”
Section: Discussionmentioning
confidence: 99%
“…cell volume, shape, and adhesion; Fig. 1) that affect visual aspect and major texture attributes of the fruit (Rose and Bennett, 1999;Cheniclet et al, 2005;Chaïb et al, 2007;Guillon et al, 2008). To get an insight into the regulation of the developmental and metabolic processes taking place in expanding fruit tissues, we analyzed at cytological, transcriptomic, and metabolic levels two major tomato fruit tissues, the mesocarp and the locular tissue, from the end of the cell division period to the end of the cell expansion period and combined these data.…”
Section: Discussionmentioning
confidence: 99%